The Shanghai Exchange Scandal and Chinese Bonds Law - Xia, Timothy Tingkang (Columbia Journal of Asian Law, 1996)
For the past sixteen years China’s economy has grown at an impressive rate. China has doubled its national wealth in just 16 years, 5 years ahead of its schedule. A profound, sustainable growth has been predicted for the coming 15 years. This enormous growth invites a rapid expansion of funding needs. China, in displaying its skill of adopting western concepts and adapting them to suit its own needs, has used its fledgling capital markets to infuse sorely needed capital into the economy. In order to tap the huge private savings of Chinese citizens, which totaled 3 trillion yuan at the end of 1995, the Chinese government began to issue Treasury bonds in 1981, which signaled the takeoff of China’s securities industry. In 1983, companies began to issue stocks in China. In August, 1986, the People’s Bank of China, Shenyang Branch, approved a pilot project for bonds trading. One month later, 5 million yuan of stocks in two collective enterprises were put on the market. The country’s first national stock exchange, the Shanghai Securities Exchange (hereinafter “SSE”), was opened on December 19, 1990. It was soon followed by the official establishment of the Shenzhen Stock Market (hereinafter the “SSM”), which opened its doors to investors on July 3, 1991. China went further in its effort to attract capital in December 1991, when it allowed the first “B shares” to be offered at the SSM to foreign investors. In January, 1992, Deng Xiaoping, the architect of the Chinese social and economic reform, called for bold experiments with the securities markets. China’s securities markets then experienced quite a bullish period from 1992 to 1994. The total value of stocks in the SSE and the SSM stood over 100 billion yuan in 1992. Average daily transactions in the Shanghai market alone reached a record of 1.5 billion yuan in early 1993, comparable to a slow day on the Hong Kong market.4 From 1981 to 1994, moreover, China had floated more than 310 billion yuan in bonds.